2006
DOI: 10.1182/blood-2006-05-021873
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 and pharmacologic study of MS-275, a histone deacetylase inhibitor, in adults with refractory and relapsed acute leukemias

Abstract: MS-275 is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(164 citation statements)
references
References 49 publications
6
154
1
1
Order By: Relevance
“…Consistent with this hypothesis, several clinical trials showed reduced toxicity with selective HDAC inhibitors relative to the pan-HDAC inhibitors. For example, hematological toxicities, anemia, and QT prolongation were absent or reduced in clinical trials with class I selective inhibitors entinostat and mocetinostat, 16,17 as compared with pan inhibitors such as SAHA. 18 In addition to their possible use as more effective clinical drugs, isoformselective HDAC inhibitors would be useful chemical tools to study HDAC cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, several clinical trials showed reduced toxicity with selective HDAC inhibitors relative to the pan-HDAC inhibitors. For example, hematological toxicities, anemia, and QT prolongation were absent or reduced in clinical trials with class I selective inhibitors entinostat and mocetinostat, 16,17 as compared with pan inhibitors such as SAHA. 18 In addition to their possible use as more effective clinical drugs, isoformselective HDAC inhibitors would be useful chemical tools to study HDAC cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be used as a tool to discern between relative contributions of these HDACs to cancer types. In addition, MS-275 has been evaluated in Phase I/II clinical trials to treat acute leukemias and solid tumors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Vorinostat as well as other HDACI such as Entinostat (MS-275) (Gojo et al, 2007) and MGCD0103 (Kell, 2007) -both of them in clinical trials (Kell, 2007;Tomillero & Moral, 2010) -have been shown to exert proapoptotic effects on pancreatic tumor cells and to chemosensitize them to gemcitabine (Arnold et al, 2007;Iwahashi et al, 2011;Sung et al, 2011). These drugs are now being tested in phase I-II trials recruiting advanced pancreatic cancer patients.…”
Section: Histone Deacetylase (Hdacs)mentioning
confidence: 99%